2008
DOI: 10.1111/j.1525-1438.2007.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid trophoblastic tumor of paracervix and parametrium

Abstract: Noh HT, Lee KH, Lee MA, Ko YB, Hwang SH, Son SK. Epithelioid trophoblastic tumor of paracervix and parametrium. Int J Gynecol Cancer 2008;18:843-846.Epithelioid trophoblastic tumor (ETT) is an unusual variant of gestational trophoblastic tumor that is closely related to choriocarcinoma and placental site trophoblastic tumor but shows different morphologic and immunohistochemical features. We report an ETT discovered in paracervix, parametrium, and periadnexal soft tissue of a 44-year-old woman. She underwent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 8 publications
4
18
1
Order By: Relevance
“…All previously reported extrauterine ETT included lung, vagina, broad ligament, fallopian tube, gallbladder, paracervix and parametrium, probably originating from uterine trophoblastic disease [6][7][8][9][10][11][12]. Pancreas metastasis in our study, to our knowledge, was the first case reported.…”
Section: Discussionmentioning
confidence: 39%
“…All previously reported extrauterine ETT included lung, vagina, broad ligament, fallopian tube, gallbladder, paracervix and parametrium, probably originating from uterine trophoblastic disease [6][7][8][9][10][11][12]. Pancreas metastasis in our study, to our knowledge, was the first case reported.…”
Section: Discussionmentioning
confidence: 39%
“…The interval between prior gestation or gestational trophoblastic tumor and ETT can range from 2 weeks to 30 years [8,9]. Extrauterine ETT in the absence of a uterine tumor has been documented in the lung, parametrial tissue, broad ligament, liver, spine, orbit and lymph nodes [8,9,10,11,12,13,14]. …”
Section: Discussionmentioning
confidence: 99%
“…Most cases present in reproductive-age women with a prior gestation. The most common presenting symptom is abnormal uterine bleeding (Noh et al, 2008;Vencken et al, 2006;Palmer et al, 2008). This case posed a diagnostic challenge because of its unusual presenting characteristics.…”
Section: Discussionmentioning
confidence: 96%
“…Epithelioid trophoblastic tumor (ETT) is an uncommon gestational trophoblastic tumor (Noh et al, 2008) which often presents as a discrete uterine mass following pregnancy with vaginal bleeding (Noh et al, 2008;Vencken et al, 2006). Here we report our experience in managing a nulligravid woman with an unusual presentation of this rare tumor type.…”
Section: Introductionmentioning
confidence: 92%